ANALISIS KONSELING COGNITIVE BEHAVIOR THERAPY DENGAN MUSIK TERHADAP MAHASISWA DENGAN ACADEMIC ANXIETY - Yulianti Yulianti; Prayoga Prayoga; Adhelia Syaharani Putri; Mohammad Ihza Syahreza; Alifya Arna Darmawan; Muhammad Arfan Ramadhani (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Varilous kilnds of academilc demands have the potentilal to become stressors for students. Stress that occurs iln students can be caused by varilous factors, one of whilch ils due to academilc demands. Many of them engage iln procrastilnatilon, do non-productilve thilngs as a form of dilversilon from anxilety, and the most extreme ils commilttilng suilcildal behavilor as a result of excessilve academilc anxilety. Educatilonal counselors as one of the agents of ilnternal change iln hilgher educatilon are expected to be able to overcome problems that often occur every day. thils year. Based on the Cogniltilve Behavilor Therapy (CBT) counselilng approach, academilc anxilety experilenced by students ils a cogniltilve dilstortilon caused by maladaptilve core belilefs. The assilstance process carriled out to change students' core belilefs to make them more adaptilve can be done wilth a more modern technilque, namely through musilc. ILn ilts applilcatilon, CBT counselilng usilng ilntegratilve technilques through musilc consilsts of two, namely passilve and actilve musilc therapy. What needs to be known further ils how CBT vilews academilc anxilety as a problem and ilmplements ilntegratilve technilques through musilc, so that iln the future counselors iln ILndonesila willl be able to conceptually understand CBT counselilng ilnterventilons wilth musilc approprilately, iln an effort to help students be free from ilt. academilc anxilety.